The Effect of Cupping Therapy on Blood pressure: Literature Review - Agung Riyanto, Dwi (KnE Social Sciences, 2023)
Hypertension is one of the diseases with the highest risk in the world for cardiovascular disease, making it a primary factor in Indonesia as it causes damage to the heart, blood vessels, kidneys, lungs, and sensory-motor nerve cells, which may lead to death. This literature review aims to identify cupping therapy for clients’ hypertension to decrease blood pressure according to results from studies from the last 5 years. Cupping therapy is one of the complementary therapies that is effective for prevention and treatment of some health problems in the body. The research method uses literature review designs as much as fifth journal from secondary databases, Google Scholar, and Science Direct on journals published between 2017 and 2022, according to keyword articles for a review. The article review uses the PICOS method in accordance with keyword of journal selection from the abstract, which include inclusion and exclusion criteria for the article to be reviewed. Overall, the journal research on cupping therapy intervention has shown results for patients with high blood pressure, so getting cupping therapy periodically can be effective in decreasing blood pressure. Keywords: cupping therapy, hypertension, complementary